Perceived Benefits of Training and Development: Employees’ Perspectives in a Primary Cooperative in the Philippines - Roberto G. Corilla Jr.; Renand T. Segundo; Leunamme G. Seguia; Shena Leyen F. Palomo; Sam Nicole N. Perez; Raymart E. Cada; Jesus Briones (Humanities, Society, and Community, 2025)
The importance of training and development in today's competitive corporate environment is widely recognized as a necessary investment in human capital, as it is believed to enhance employee performance, increase engagement, and promote organizational agility. This study evaluated the perceived benefits of training and development in a primary cooperative in the Philippines. This study employed a descriptive-quantitative research design to assess the perceptions of 113 employees regarding the benefits of training and development, using an adopted survey questionnaire prepared in Google Forms. The distribution of questionnaires to the target respondents was conducted via electronic mail and Messenger. The data were analyzed using frequency, percentage, weighted mean, and ANOVA. The study confirmed that the cooperative's employees are predominantly young, with a slightly higher proportion of male employees, and a workforce primarily composed of rank-and-file staff who are just starting their careers at the cooperative. Regarding the benefits of training and development, employees perceived its positive impact across all dimensions, which include goal achievement, collaboration and communication, level of quality and efficiency, and personal and professional attributes. Moreover, the study revealed that there are no significant differences in the perceived benefits of training and development when employees are grouped according to their profile. Finally, the researchers proposed strategies to enhance further the perceived benefits of training and development in the primary cooperative subject. This study can serve as a valuable reference for human resource managers in designing, implementing, monitoring, and evaluating training and development programs provided to employees.